Comparative Analysis of Patients with Robotic Hiatal Hernia Repairs with and without Collis Gastroplasty. Issue 2 (February 2022) - Perrone, John A.; Yee, Stephanie; Guerrero, Manrique; Wang, Antai; Hanley, Brian; Zuberi, Jamshed; Damani, Tanuja
Introduction: After extensive mediastinal dissection fails to achieve adequate intra-abdominal esophageal length, a Collis gastroplasty(CG) is recommended to decrease axial tension and reduce hiatal hernia recurrence. However, concerns exist about staple line leak, and long-term symptoms of heartburn and dysphagia due to the acid-producing neoesophagus which lacks peristaltic activity. This study aimed to assess long-term satisfaction and GERD-related quality of life after robotic fundoplication with CG (wedge fundectomy technique) and to compare outcomes to patients who underwent fundoplication without CG. Outcomes studied included patient satisfaction, resumption of proton pump inhibitors (PPI), length of surgery (LOS), hospital stay, and reintervention. Methods: This was a single-center retrospective analysis of patients from January 2017 through December 2018 undergoing elective robotic hiatal hernia repair and fundoplication. 61 patients were contacted for follow-up, of which 20 responded. Of those 20 patients, 7 had a CG performed during surgery while 13 did not. There was no significant difference in size and type of hiatal hernias in the 2 groups. These patients agreed to give their feedback via a GERD health-related quality of life (GERD HRQL) questionnaire. Their medical records were reviewed for LOS, length of hospital stay (LOH), and reintervention needed. Statistical analysis was performed using SPSS v 25. Satisfaction and need for PPIs were compared between the treatment and control groups using the chi-square test of independence. Results: Statistical analysis showed that satisfaction with outcome and PPI resumption was not significantly different between both groups ( P > .05). There was a significant difference in the average ranks between the 2 groups for the question on postoperative dysphagia on the follow-up GERD HRQL questionnaire, with the group with CG reporting no dysphagia. There were no significant differences in the average ranks between the 2 groups for the remaining 15 questions ( P > .05). The median LOS was longer in patients who had a CG compared to patients who did not (250 vs. 148 min) ( P = .01). The LOH stay was not significantly different ( P > .05) with a median length of stay of 2 days observed in both groups. There were no leaks in the Collis group and no reoperations, conversions, or blood transfusions needed in either group. Conclusion: Collis gastroplasty is a safe option to utilize for short esophagus noted despite extensive mediastinal mobilization and does not adversely affect the LOH stay, need for reoperation, or patient long-term satisfaction.